Foraging behaviour of the Eurasian Three-toed Woodpecker Picoides tridactylus in its peak abundance after wildfire - Versluijs, Martijn; Mikusinski, Grzegorz; Roberge, Jean-Michel (Ardea, 2023)
In the boreal biome, forest fires are the most important natural disturbance influencing tree substrate availability and quality for a range of specialized species. This includes the Eurasian Three-toed Woodpecker Picoides tridactylus, which is known to promptly utilize burned forest habitats. However, there are no studies addressing the foraging behaviour of this woodpecker in forests affected by wildfire. Such knowledge could assist the development of efficient post-fire management strategies which are in line with biodiversity conservation objectives. This study describes the foraging behaviour of the Eurasian Three-toed Woodpecker during the breeding season in a forest area of 13,100 ha in southcentral Sweden affected by a major wildfire in 2014. During the second breeding season after fire, we used instantaneous sampling where we observed the foraging behaviour of 28 individuals during a total of 1681 observation minutes. Our results suggest that Norway Spruce Picea abies and larger diameter trees (DBH > 25 cm) are important foraging substrates. However, data on time spent foraging on the different substrates suggest that Scots Pines Pinus sylvestris also are important. In particular, we identified the importance of the root collars, where excavation into sapwood was the main foraging method. Our study was performed during a clearly visible peak of Eurasian Three-toed Woodpecker abundance and this may suggest that the level of food resources available was very high which led to observed foraging patterns not necessarily observed in other types of habitats. Peer reviewed